2017
DOI: 10.1111/jace.14664
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐potassium niobate nanorods with various crystal structures and their application to nanogenerator

Abstract: Na 1Àx K x )NbO 3 (NKN) nanorods with an orthorhombic (OR) structure, a rhombohedral (RH) structure, or a polymorphic phase (PP) structure, which contains both OR and RH structures, are prepared. The presence of RH and PP NKN nanorods is explained by the existence of OH À defects at the O 2À sites of the NKN nanorods. The PP NKN nanorods grown on a Nb 5+ -doped SrTiO 3 substrate show the largest piezoelectric strain constant of 175 pm/V because they have more directions for dipole rotation than OR and RH NKN n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…HaiBo et al (2017) found that polymorphic phase sodium-potassium niobate (NKN) nanorods have the most significant piezoelectric strain constant (175 pm/V) as they have more directions for dipole rotation than the nanogenerators with rhombohedral or orthorhombic nanorods [45]. Their experiment, using 0.7 g of PP (polymorphic phase) NKN nanorods, showed a maximum open-circuit voltage of 35 V and a short circuit current of 5.0 at a strain of 2.13% and an average strain rate of 3.7% s −1 .…”
Section: Nanogenerators Based On Piezoelectric Effectmentioning
confidence: 99%
“…HaiBo et al (2017) found that polymorphic phase sodium-potassium niobate (NKN) nanorods have the most significant piezoelectric strain constant (175 pm/V) as they have more directions for dipole rotation than the nanogenerators with rhombohedral or orthorhombic nanorods [45]. Their experiment, using 0.7 g of PP (polymorphic phase) NKN nanorods, showed a maximum open-circuit voltage of 35 V and a short circuit current of 5.0 at a strain of 2.13% and an average strain rate of 3.7% s −1 .…”
Section: Nanogenerators Based On Piezoelectric Effectmentioning
confidence: 99%
“…Piezoelectric and ferroelectric nanowires are promising candidates for nanoscale functional applications, including biomedical electronics, self-powered wearable and human activity monitoring devices, and multienergy harvesting . For example, piezoelectric zinc-oxide nanowires were found to function as nanogenerators for self-powered nanodevices where they can produce the output current of 0.6 μA and associated current density of 20 μA/cm 2 , while sodium–potassium niobate nanorods were reported to have the short-circuit current of 5.0 μA .…”
mentioning
confidence: 99%
“…Piezoelectric and ferroelectric nanowires are promising candidates for nanoscale functional applications, including biomedical electronics, self-powered wearable and human activity monitoring devices, and multienergy harvesting . For example, piezoelectric zinc-oxide nanowires were found to function as nanogenerators for self-powered nanodevices where they can produce the output current of 0.6 μA and associated current density of 20 μA/cm 2 , while sodium–potassium niobate nanorods were reported to have the short-circuit current of 5.0 μA . KNbO 3 nanowire composite structures were reported to function as flexible pyroelectric nanogenerators, while ferroelectric PZT nanowires were found to exhibit dramatically high pyroelectric open-circuit voltage and short-circuit current in a pyroelectric nanogenerator .…”
mentioning
confidence: 99%
See 1 more Smart Citation